Star formation law in the epoch of reionization from [C ii] and C iii] lines. (19th March 2020) - Vallini, L; Ferrara, A; Pallottini, A; Carniani, S; Gallerani, S
ABSTRACT: We present a novel method to simultaneously characterize the star formation law and the interstellar medium properties of galaxies in the epoch of reionization (EoR) through the combination of [C ii ] 158 μ m (and its known relation with star formation rate) and C iii ] λ1909 Å emission line data. The method, based on a Markov chain Monte Carlo algorithm, allows us to determine the target galaxy average density, n, gas metallicity, Z, and 'burstiness' parameter, κs, quantifying deviations from the Kennicutt–Schmidt relation. As an application, we consider COS-3018 ( z = 6.854), the only EoR Lyman Break Galaxy so far detected in both [C ii ] and C iii ]. We show that COS-3018 is a moderate starburst (κs ≈ 3), with $Z ≈ 0.4 \, Z_{\odot }$, and $n ≈ 500\, {\rm cm^{-3}}$ . Our method will be optimally applied to joint ALMA and James Webb Space Telescope targets.